1993
DOI: 10.1088/0268-1242/8/12/010
|View full text |Cite
|
Sign up to set email alerts
|

Band offset of GaAs-GaInP heterojunctions

Abstract: N +GaAs-n GalnP lattice-matched heterostructures, grown by metalorganic vapour phase epitaxy, have been studied by capacitance-voltage, current-voltage and current-temperature techniques. This allowed the determination of the conduction band offset in three different anti independent ways. The value obtained (0.24425 eV) ha? been verified by photoluminescence and photoluminescence excitation on a 9OA thick GaAs weii in GainP grown under t h e same conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The band gap for the lattice-matched alloy Ga 0.51 In 0.49 P is 0.49 eV higher than that of GaAs in the temperature range up to 300 K. An early Shubnikov-de Haas experiment yielded a CBO of 0.39 eV. 824 Watanabe and Ohba measured a smaller CBO of 0.19 eV using the conduction-voltage profiling technique, 825 which is in good agreement with similar studies by Rao et al, 826 Lee et al, 827 and Feng et al, 828 and with the DLTS measurements of Biswas et al 829 Other experiments found that the VBO consitutes an even larger fraction of the band gap discontinuity (⌬E v ϭ0.32-0.46 eV). [830][831][832][833][834][835][836][837] One study obtained a small CBO for the GaInP/AlGaAs heterojunction in the low-Al-fraction limit, 838 while other recent reports have found values intermediate between the two limits.…”
Section: Gainpõalinpõgaassupporting
confidence: 85%
“…The band gap for the lattice-matched alloy Ga 0.51 In 0.49 P is 0.49 eV higher than that of GaAs in the temperature range up to 300 K. An early Shubnikov-de Haas experiment yielded a CBO of 0.39 eV. 824 Watanabe and Ohba measured a smaller CBO of 0.19 eV using the conduction-voltage profiling technique, 825 which is in good agreement with similar studies by Rao et al, 826 Lee et al, 827 and Feng et al, 828 and with the DLTS measurements of Biswas et al 829 Other experiments found that the VBO consitutes an even larger fraction of the band gap discontinuity (⌬E v ϭ0.32-0.46 eV). [830][831][832][833][834][835][836][837] One study obtained a small CBO for the GaInP/AlGaAs heterojunction in the low-Al-fraction limit, 838 while other recent reports have found values intermediate between the two limits.…”
Section: Gainpõalinpõgaassupporting
confidence: 85%
“…4 Time-resolved studies of the low energy PL peak show long nonexponential decay times indicating spatial separation of the electrons and holes. 10 There is even evidence for type II band alignment. Based on these observations, it has been proposed that the samples are not uniformly ordered but exhibit domains of varying degree of order 7 and that the interface between ordered and disordered GaInP has a type II alignment 6,8,9 with the valence band maximum in the disordered and the conduction band minimum in the ordered region.…”
Section: Polarization Fields and Band Offsets In Gainp/gaas And Ordermentioning
confidence: 99%
“…However, the offsets of the GaAs/GaInP heterojunction are poorly known, as the reported values of the conduction band offset ⌬E C range from 30 to 390 meV. 2 The wide distribution of measured values may be due to the differences in the samples or in the measuring techniques themselves. We have measured both p-p and n-n type heterojunctions individually, in order to obtain independent values for both the valence band and the conduction band offsets.…”
Section: Introductionmentioning
confidence: 99%